Hubungan antara pengurusan masa dengan tahap ketegangan (stress) di kalangan guru besar Sekolah Rendah di Bahagian Kuching / Samarahan, Di Sarawak - Bunsie, Anak Tunton. (1998)
This study analyses the relationship between time management and the degree of stress among Principals of Primary Schools in Kuching / Samarahan Division. Specifically, it is aimed at identifying the relationship between the causes and the degree of stress of working in the office and working outside the office and the techniques of time management. A total of 214 Principals of Primary Schools with different background and experiences were sampled. Information was collected using quesionnaire, which has been translated and modified from Tanner and Atkins (1990)